Specific FAHFAs predict worsening glucose tolerance in non-diabetic relatives of people with Type 2 diabetes - Ismail Syed; Ken Sluis; Pratik Aryal; Zachary Solomon; Rucha Patel; Srihari Konduri; Dionicio Siegel; Ulf Smith; Barbara B. Kahn (Journal of Lipid Research)
There is a growing need for early biomarkers for Type 2 diabetes (T2D). Fatty-Acid-Hydroxy-Fatty-Acids (FAHFAs) are bioactive lipids with >580 regioisomers in human tissues. FAHFAs such as Palmitic Acid Hydroxy Stearic Acids (PAHSAs) are anti-diabetic and anti-inflammatory. PAHSA concentrations in human serum and adipose tissue strongly correlate with insulin sensitivity. Since PAHSAs and palmitic acid hydroxy oleic acids (PAHOAs) are among the most abundant FAHFAs in human serum, we investigated whether they predict worsening glucose tolerance in first-degree relatives of people with T2D. All participants had normal glucose tolerance (NGT) at baseline; 27 remained NGT (NGT-NGT) and 21 developed impaired glucose tolerance (NGT-IGT). In NGT-NGT, total PAHSA and PAHSA regioisomer concentrations were unchanged from baseline to follow-up, while in NGT-IGT participants, most PAHSA regioisomers decreased. The initial total PAHSAs, 5-PAHSA, and 9-PAHSA, and changes in these correlated inversely with worsening glucose tolerance. Low total PAHSA concentrations at baseline and the decrease in total PAHSAs, 5-PAHSAs, and 9-PAHSAs over time predicted IGT independent of initial BMI or %body fat, change in BMI or in %body fat, initial fasting glucose, fasting insulin, or triglyceride/HDL ratio. In contrast, baseline and follow-up total PAHOA and PAHOA regioisomer levels were higher in NGT-IGT than NGT-NGT, and some PAHOA regioisomers increased during follow-up in NGT-IGT. Higher initial total PAHOAs predicted IGT independent of the same clinical variables. Thus, lower serum PAHSAs and higher PAHOAs predict worsening glucose tolerance/IGT independent of BMI, %body fat, or change in these parameters, even in lean, relatively young people.